Coating composition for container glass
Patent Information
- Application Number
- CN202580020504.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-11
- Filing Date
- 2025-03-06
- Publication Date
- 2026-10-09
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] The present invention relates to a method, coated articles, glass coating compositions, and uses of glass coating compositions, the method comprising providing a coating composition comprising a reactive binder system (B), applying the coating composition to the glass surface of a container glass article to form a coating and curing it.
[0002] Container glass is an important packaging material, especially for the food and beverage, cosmetics, and perfume industries. Glass is an advantageous packaging material because it is 100% recyclable. Therefore, a sophisticated collection and recycling system for waste glass is necessary. Since its color cannot be removed or can only be removed with great effort, colored glass must be strictly separated from colorless glass. For example, the color is often a result of metal oxides contained in the glass, such as iron oxide, copper oxide, and chromium oxide (iii).
[0003] US 2023 / 0101908 teaches how to spray a primer composition onto the surface of a glass container and heat the primer. The primer composition contains an aqueous dispersion of polyacrylic acid. This allows the coated glass container to withstand direct digital printing.
[0004] The most common liquid adhesive systems used in such thermosetting coating compositions are polyesters and polyacrylates. These polymers are thermally crosslinked with, for example, melamine-formaldehyde resins. Hydroxyl-functionalized styrene-acrylic dispersions are known for use in water-based 1K thermosetting glass coatings.
[0005] Known crosslinking agents contain N-hydroxymethyl groups, such as amino plastics, which are reaction products of formaldehyde with substances like urea, dicyandiamide, and aminotriazines such as melamine. All of these systems release formaldehyde during crosslinking. Therefore, the search for new "formaldehyde-free" systems has been ongoing for a long time.
[0006] The purpose of this invention is to provide a novel formaldehyde-free adhesive system for coating container glass, which has comparable or better application characteristics.
[0007] In addition, the hardened coating produced using this adhesive system should have good elasticity, good adhesion to the substrate, high gloss, excellent surface hardness, and good water resistance.
[0008] We have discovered that these objectives are surprisingly achieved through the following method, which includes:
[0009] A coating composition comprising an adhesive system (B) is provided, wherein the adhesive system (B) comprises
[0010] (a) Aqueous polymer dispersion (P), and
[0011] (b) at least one amine and / or amide having at least two hydroxyl groups, based on 1% to 12% by weight of the total weight of the olefinically unsaturated monomer M and polymer A.
[0012] The aqueous polymer dispersion (P) is prepared by free radical-initiated emulsion polymerization of the following olefinically unsaturated monomer M in an aqueous medium in the presence of polymer A:
[0013] Styrene and (meth)acrylic acid C1-C by weight: 65% to 95% 10 -Alkyl esters and / or (meth)acrylic acid C5-C 10 -Cycloalkyl esters;
[0014] One or more hydroxyl-functionalized (meth)acrylates, (meth)acrylates glycidyl esters and / or (meth)acrylamides, by weight, comprising 5% to 35% of the following:
[0015] One or more mono-olefin unsaturated carboxylic acids and / or mono-olefin unsaturated sulfonic acids, by weight, from 0% to 5%.
[0016] One or more diene-bonded unsaturated monomers, comprising 0% to 2% by weight, and
[0017] The total amount of monomer M is 100% by weight.
[0018] Polymer A has the following monomeric structural units:
[0019] At least one olefinically unsaturated monocarboxylic acid and / or dicarboxylic acid (monomer A1) in an amount of 80% to 100% by weight, and
[0020] From 0% to 20% by weight of at least one other olefinic unsaturated monomer (monomer A2) different from monomer A1.
[0021] The quantity is based on the total amount of all monomeric structural units in polymer A in each case.
[0022] The coating composition is applied to the glass surface of a container glass article to form a coating, and the coating is cured by treating the coating at a temperature in the range of 130°C to 350°C.
[0023] The present invention also relates to coated articles, glass coating compositions themselves, and the use of glass coating compositions for coating container glass articles.
[0024] If the solids content of an aqueous dispersion is mentioned as a percentage by weight, it is based on the weight of the aqueous dispersion.
[0025] In the following text, compounds derived from acrylic acid and methacrylic acid are partially shortened by inserting the syllable "(methyl)" into the compounds derived from acrylic acid.
[0026] The polymer dispersion (P) is prepared by free radical-initiated emulsion polymerization of the following olefinically unsaturated monomer M in an aqueous medium in the presence of polymer A:
[0027] Styrene and (meth)acrylic acid C1-C by weight: 65% to 95% 10 -Alkyl esters and / or (meth)acrylic acid C5-C 10 -Cycloalkyl ester (monomer M1);
[0028] One or more (meth)acrylate hydroxy (C2-C4)-alkyl esters, (meth)acrylate glycidyl esters, and / or (meth)acrylamide (monomer M2) by weight, comprising 5% to 35% of each.
[0029] One or more mono-olefin unsaturated carboxylic acids and / or mono-olefin unsaturated sulfonic acids (monomer M3) by weight, ranging from 0% to 5%.
[0030] 0% to 2% by weight of diene-bonded unsaturated monomer (monomer M4), and
[0031] The total amount of monomer M is 100% by weight.
[0032] Assume that polymer A helps stabilize the polymer particles of polymer M. For simplicity, the polymer formed from such olefinically unsaturated monomers M can be referred to as "polymer M". In the resulting polymer, polymer A exhibits strong bonding (e.g., covalent or ionic bonding) with polymer M made from monomer M, or is otherwise well complexed or entangled with polymer M, making it impossible to extract from the cured coating film. Without being bound by theory, it can be said that the polymer of the aqueous dispersion (P) has a multi-level polymer morphology, but it is believed that the polymer does not possess a conventional core-shell structure. However, in a manner more similar to conventional shell polymers, polymer A can act as a hydrophilic interface between polymer M and the aqueous dispersion medium after polymer M is formed.
[0033] Regarding monomer M, the following alkyl groups are preferably straight-chain or branched C1-C2 alkyl groups. 10 Alkyl groups, such as methyl, ethyl, n-propyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, 2-ethylhexyl, and 2-octyl.
[0034] Suitable (meth)acrylic acid C5-C 10 -Cycloalkyl esters are cyclohexyl methacrylate, isobornyl methacrylate, 3,3,5-trimethylcyclohexyl methacrylate and dicyclopentadiene acrylate.
[0035] Polymer M is composed of styrene and (meth)acrylic acid C1-C 10 -Alkyl esters and / or (meth)acrylic acid C5-C 10 -Cycloalkyl esters are formed as the main monomer M1. Preferred monomers M1 are styrene, cyclohexyl methacrylate and C1-C8-alkyl esters of (meth)acrylate, especially methyl methacrylate, 2-octyl acrylate and 2-ethylhexyl acrylate and n-butyl methacrylate. Particularly preferred monomers M1 are styrene, methyl methacrylate and n-butyl acrylate.
[0036] The comonomer M2 is selected from the group consisting of hydroxy (C2-C4)-alkyl esters of (meth)acrylate, glycidyl esters of (meth)acrylate, and (meth)acrylamide.
[0037] Suitable hydroxyl-functionalized (meth)acrylates are 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, 4-hydroxybutyl methacrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol mono(meth)acrylate. 2-hydroxyethyl acrylate and 2-hydroxyethyl methacrylate are particularly preferred.
[0038] The comonomer M3 is selected from the group consisting of monoene-bonded unsaturated carboxylic acids and monoene-bonded unsaturated sulfonic acids.
[0039] Suitable monoene-bonded unsaturated carboxylic acids are C3-C6 α,β-monoene-bonded unsaturated monocarboxylic acids, such as acrylic acid and methacrylic acid. If desired, these acids may also exist in the polymer in part or entirely as salts. The acidic form is preferred.
[0040] Suitable mono-olefinic unsaturated sulfonic acids are styrene sulfonic acid, acrylamidopropyl sulfonic acid, and vinyl sulfonic acid. If desired, these acids may also exist in the polymer in part or entirely as salts. The acidic form is preferred.
[0041] Preferably, the polymer (M) is prepared by polymerization of the following monomer M:
[0042] Styrene and (meth)acrylic acid C1-C by weight: 80% to 95% 10 -Alkyl esters and / or (meth)acrylic acid C5-C 10 -Cycloalkyl esters;
[0043] 5% to 20% by weight of one or more (meth)acrylate hydroxy (C2-C4)-alkyl esters, (meth)acrylate glycidyl esters and / or (meth)acrylamide,
[0044] One or more mono-olefin unsaturated carboxylic acids and / or mono-olefin unsaturated sulfonic acids, by weight, from 0% to 5%.
[0045] 0% to 2% by weight of diene-bonded unsaturated monomers, and
[0046] The total amount of monomer M is 100% by weight.
[0047] According to a preferred embodiment, the polymer (M) is prepared by polymerization of the following monomer M:
[0048] 80% to 95% by weight of one or more monomers M1, wherein the one or more monomers M1 are selected from the group consisting of styrene, C1-C8 alkyl esters of (meth)acrylate and cyclohexyl methacrylate.
[0049] 5% to 20% by weight of one or more monomers M2, wherein the monomers M2 are selected from the group consisting of hydroxy (C2-C4)-alkyl esters of (meth)acrylate, glycidyl esters of (meth)acrylate, and (meth)acrylamide.
[0050] One or more monomers M3, comprising 0% to 5% by weight, wherein the monomers M3 are selected from the group consisting of monoene-bonded unsaturated carboxylic acids and monoene-bonded unsaturated sulfonic acids.
[0051] One or more diene-bonded unsaturated monomers M4, comprising 0% to 2% by weight, and
[0052] The total amount of monomer M is 100% by weight.
[0053] According to a preferred embodiment, the polymer (M) is prepared by polymerization of the following monomer M:
[0054] 80% to 95% by weight of one or more monomers M1, wherein the one or more monomers M1 are selected from the group consisting of styrene, methyl methacrylate, 2-octyl acrylate, 2-ethylhexyl acrylate and (meth)acrylate n-butyl acrylate.
[0055] 5% to 20% by weight of one or more monomers M2, wherein the monomers M2 are selected from the group consisting of hydroxyethyl (meth)acrylate and glycidyl (meth)acrylate.
[0056] One or more monomers M3, comprising 0% to 5% by weight, wherein the monomers M3 are selected from the group consisting of monoene-bonded unsaturated carboxylic acids and monoene-bonded unsaturated sulfonic acids.
[0057] One or more diene-bonded unsaturated monomers M4, comprising 0% to 2% by weight, and
[0058] The total amount of monomer M is 100% by weight.
[0059] Polymer A has the following monomer structural units:
[0060] At least one olefinically unsaturated monocarboxylic acid and / or dicarboxylic acid (monomer A1) in an amount of 80% to 100% by weight, and
[0061] From 0% to 20% by weight of at least one other olefinic unsaturated monomer (monomer A2) different from monomer A1.
[0062] This amount is based on the total amount of all monomeric structural units in polymer A in each case.
[0063] In the preparation of polymer A, its anhydride, such as maleic anhydride, acrylic anhydride, or methacrylic anhydride, can certainly be used in place of the acid or in conjunction with the acid. Even if the anhydride is used as the starting monomer for polymerization, the unit present in the polymer is its corresponding acid. If desired, these acids can also exist in the polymer in part or entirely in the form of salts. The acidic form is preferred.
[0064] Useful monomers A1 particularly include α,β-monoolefinically unsaturated monocarboxylic and dicarboxylic acids having 3 to 6 carbon atoms, possible anhydrides of these monocarboxylic and dicarboxylic acids, and water-soluble salts of these monocarboxylic and dicarboxylic acids, especially alkali metal salts of these monocarboxylic and dicarboxylic acids, examples being acrylic acid, methacrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, and anhydrides of these acids (e.g., maleic anhydride), as well as sodium or potassium salts of the aforementioned acids. Acrylic acid, methacrylic acid, maleic acid, and / or maleic anhydride are particularly preferred, and (meth)acrylic acid is especially preferred.
[0065] Preferred polymer A is polymer A having the following monomeric structural units:
[0066] 80% to 100% by weight of acrylic acid, methacrylic acid and / or itaconic acid
[0067] Maleic acid, 0% to 20% by weight
[0068] 0% to 10% by weight of at least one other monomer different from monomer A1;
[0069] This amount is based on the total amount of all monomeric structural units in polymer A in each case.
[0070] The useful monomer A2 used to prepare polymer A is a monomer different from monomer A1. At least one monomer A2 used according to the invention is in particular an olefinically unsaturated compound that can be easily copolymerized with monomer A1 in a radical manner, such as ethylene; vinyl aromatic monomers such as styrene, α-methylstyrene, o-chlorostyrene, or vinyltoluene; vinyl halides such as vinyl chloride or vinylidene chloride; esters derived from vinyl alcohols and monocarboxylic acids having 1 to 18 carbon atoms (e.g., vinyl acetate, vinyl propionate, vinyl butyrate, vinyl laurate, and vinyl stearate); and esters derived from, preferably, α,β-monoolefinically unsaturated compounds having 3 to 6 carbon atoms. Saturated monocarboxylic acids and dicarboxylic acids (specific examples are acrylic acid, methacrylic acid, maleic acid, fumaric acid, and itaconic acid) with esters of alkanols typically having 1 to 12, preferably 1 to 8, and especially 1 to 4 carbon atoms (specific examples are methyl, ethyl, n-butyl, isobutyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, and 2-ethylhexyl esters of acrylic acid and methacrylic acid, and dimethyl or di-n-butyl esters of fumaric acid and maleic acid); α,β-monoolefinically unsaturated nitrile (e.g., acrylonitrile, methacrylonitrile, fumaric acid, maleic acid); and C 4-8 Conjugated dienes such as 1,3-butadiene (butadiene) and isoprene. The monomers mentioned are typically the principal monomers, and these monomers combine to form a total weight percentage of ≥50%, preferably ≥80%, and particularly preferably ≥90% of monomer A2, or essentially form the entirety of monomer A2. The solubility of these monomers in water under standard conditions [20°C, 1 atm (absolute)] is typically only moderate to low.
[0071] Under the above conditions, monomer A2 with high water solubility is those monomers containing at least one sulfonyl group and / or its corresponding anion or at least one amide group and / or urea group, or derivatives thereof. Examples include acrylamide and methacrylamide; and vinyl sulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, styrene sulfonic acid, and their water-soluble salts. The above-mentioned water-soluble monomer A2 is generally present as a modifying monomer only in an amount of ≤10% by weight, preferably ≤5% by weight, and particularly preferably ≤3% by weight based on the total amount of monomer A2.
[0072] According to the invention, the copolymerization ratio of monomer A2 in polymer A is 0% to 20% by weight, advantageously ≤10% or ≤5% by weight and ≥0.1% by weight. In another advantageous embodiment, polymer A does not contain any monomer A2 in copolymer form at all. Thus, polymer A is formed to a degree of ≥80% by weight, advantageously ≥90% or ≥95% by weight, and in another embodiment to a degree of 100% by weight of monomer A1 in copolymer form, particularly preferred monomer A1 being acrylic acid, methacrylic acid, maleic acid and / or maleic anhydride.
[0073] The polymer A used according to the invention is typically prepared by free radical-initiated polymerization of monomer A in an aqueous medium. Advantageously, polymer A is prepared in the presence of at least one free radical chain transfer agent (particularly preferred being a sulfur-, nitrogen-, and / or phosphorus-containing free radical chain transfer agent having a solubility of ≥5 g / 100 g in deionized water at 20 °C and 1 atm).
[0074] The basic principles underlying the preparation of polymer A are familiar to those skilled in the art (see Example A. Echte, Handbuch der Technischen Polymerchemie [Handbook of Industrial PolymerChemistry], Chapter 6, VCH, Weinheim, 1993 or B. Vollmert, Grundriss der Makromolekularen Chemie [Principles of Macromolecular Chemistry], Volume 1, E. Vollmert Verlag, Karlsruhe, 1988).
[0075] Sulfur-containing free radical chain transfer agents that may be used are, for example: mercaptoalkanols, such as 2-mercaptoethanol, 2-mercaptopropanol or 3-mercaptopropanol; alkali metal bisulfites, such as sodium bisulfite or potassium bisulfite; and thiosulfate and its alkali metal salts; or 3-mercapto-2-aminopropionic acid (cysteine), 3-mercaptopropionic acid, thioglycolic acid; nitrogen-containing free radical chain transfer agents used are, for example, hydroxylamine (ammonium) compounds such as hydroxyl ammonium sulfate, and phosphorus-containing free radical chain transfer agents used are, for example, phosphorous acid, hypophosphorous acid, metaphosphorous acid, orthophosphoric acid, pyrophosphoric acid or polyphosphoric acid and their alkali metal salts (especially their sodium or potassium salts, preferably sodium hypophosphite or sodium dihydrogen phosphate).
[0076] Particularly advantageously, the free radical chain transfer agent is selected from: hypophosphite and its alkali metal salts (especially sodium hypophosphite), alkali metal bisulfite (especially sodium bisulfite), hydroxyl ammonium sulfate and / or 2-mercaptoethanol.
[0077] In the preparation of polymer A, it is advantageous that the weight-average molecular weight of polymer A is ≥1000 and ≤50000 g / mol, advantageously ≥2000 g / mol and ≤30000 g / mol, and especially advantageously ≥3000 g / mol and ≤30000 g / mol.
[0078] The weight-average molecular weight of polymer A was determined in a manner familiar to those skilled in the art by gel permeation chromatography (linear column: 8 mm × 30 mm column of sulfonated styrene-divinylbenzene copolymer network, eluent: 0.1 mol / L sodium hydroxide solution in deionized water, flow rate: 0.8 mL / min, detector: differential refractometer DRI Agilent 1200 from Agilent Technologies, internal standard / calibration material: sodium polyacrylate).
[0079] Monomer M is polymerized by free radical polymerization in an aqueous medium in the presence of polymer A to produce an aqueous polymer dispersion (P). The aqueous polymer dispersion (P) is prepared by aqueous emulsion polymerization, which can be carried out in batch, semi-continuous, or continuous processes. Preferably, no additional emulsifier is added to stabilize the emulsion other than polymer A.
[0080] According to another possibility, polymer M is prepared using additional dispersing agents besides polymer A. As dispersing agents, it is preferable to use only emulsifiers, whose relative molecular weight is typically less than 2000 compared to the protective colloid. These can be anionic, cationic, or nonionic. When using mixtures of surfactants, the components must undoubtedly be compatible with each other; if in doubt, this can be verified through several preliminary tests. Generally, anionic emulsifiers are compatible with each other and with nonionic emulsifiers. This also applies to cationic emulsifiers, while anionic and cationic emulsifiers are generally incompatible with each other. Commonly used emulsifiers are, for example, ethoxylated monoalkylphenols, dialkylphenols, and trialkylphenols (EO degree: 3 to 50, alkyl group: C4 to C5). 12 ), ethoxylated fatty alcohols (EO degree: 3 to 50; alkyl groups: C8 to C5) 36 ) and alkyl sulfates (alkyl groups: C8 to C9) 12 Alkali metal salts and ammonium salts, and ethoxylated alkanols (EO degree: 4 to 30, alkyl group: C 12 To C 18 ) and ethoxylated alkylphenols (EO degree: 3 to 50, alkyl group: C4 to C5) 12Alkali metal salts and ammonium salts of sulfate monoesters, alkyl sulfonic acids (alkyl group: C 12 To C 18 Alkali metal salts and ammonium salts, and alkylaryl sulfonic acids (alkyl groups: C9 to C10). 18 Alkali metal salts and ammonium salts of ). Other suitable emulsifiers can be found in Houben-Weyl, Methoden der organischen Chemie, Vol. XIV / 1, Makromolekulare Stoffe [Macromolecular Compounds], pp. 192-208, Georg-Thieme-Verlag, Stuttgart, 1961.
[0081] When using emulsifiers according to the present invention, anionic and / or nonionic emulsifiers are advantageously used.
[0082] In a particular embodiment of the invention, the emulsifiers used are those incorporated into the polymer during free radical emulsion polymerization. These are typically compounds having at least one free radical polymerizable group and at least one emulsifying group, wherein the free radical polymerizable group is preferably selected from the group consisting of allyl, acrylate, methacrylate and vinyl ether, and the emulsifying group is preferably selected from the group indicated above.
[0083] These emulsifiers are, for example, incorporable emulsifiers with the following trademarks: Bisomer from Laporte. ® MPEG 350 MA; Hitenol from Dai-Ichi Kogyo Seiyaku Co., Ltd. ® BC-20 (APEO), Hitenol ® BC-2020, Hitenol ® KH-10 or Noigen ® RN-50 (APEO); Maxemul from Croda ® 6106, Maxemul ® 6112, Maxemul ® 5010, Maxemul ® 5011; Sipomer from Rhodia ® PAM 100, Sipomer ® PAM 200, Sipomer ® PAM 300, Sipomer ® PAM 4000, Sipomer ® PAM 5000; Adeka from Adeka ®Reasoap ® PP-70, Adeka ® Reasoap ® NE-10, Adeka ® Reasoap ® NE-20, Adeka ® Reasoap ® NE-30, Adeka ® Reasoap ® NE-40, Adeka ® Reasoap ® SE-10N, Adeka ® Reasoap ® SE-1025A, Adeka ® Reasoap ® SR-10, Adeka ® Reasoap ® SR-1025, Adeka ® Reasoap ® SR-20, Adeka ® Reasoap ® ER-10, Adeka ® Reasoap ® ER-20, Adeka ® Reasoap ® ER-30, Adeka ® Reasoap ® ER-40; Pluriol from BASF SE ® A 010 R, Pluriol ® A 12 R, Pluriol ® A 23 R, Pluriol ® A 46 R, Pluriol ® A 750 R, Pluriol ® A 950 R, Pluriol ® A590 I, Pluriol ® A 1190 I, Pluriol ® A 590 V, Pluriol ® A 1190 V, Pluriol ® A 5890 V, Pluriol ®A 308 R and DAA ES 8761; Latemul from Kao ® S 180 A and Latemul ® S 180; Eleminol from Sanyou Kasei ® JS-2; and Aquaron from Daiichi Kogyou Seiyaku ® HS-1025.
[0084] The polymerization is carried out in the presence of a radical-forming compound (initiator). These compounds can be peroxides, azo compounds, or redox initiator systems. All of these types of initiators are well known to those skilled in the art and are described, for example, in US 6,841,608. Depending on the monomers used in the polymerization, the amount of these initiators required is preferably from 0.05% to 10% by weight, and particularly preferably from 0.2% to 5%.
[0085] Initiators can be used alone or in mixtures of each other; an example is a mixture of hydrogen peroxide and sodium persulfate. For polymerization in an aqueous medium, water-soluble initiators are preferred.
[0086] To prepare polymers with low average molecular weights, it is generally wise to copolymerize in the presence of a regulator (free radical chain transfer agent). Common regulators for this purpose include, for example, organic compounds containing SH groups, such as 2-mercaptoethanol, 2-mercaptopropanol, mercaptoacetic acid, tert-butylthiol, n-octylthiol, n-dodecylthiol, and tert-dodecylthiol; and hydroxyammonium salts such as hydroxyammonium sulfate, formic acid, sodium bisulfite, or isopropanol. Polymerization regulators are typically used in amounts from 0.05% to 5% by weight of the monomer.
[0087] To prepare copolymers with relatively high molecular weights, it is generally wise to polymerize in the presence of a crosslinking agent. Such crosslinking agents are compounds having two or more olefinically unsaturated groups, such as, for example, diacrylates or dimethacrylates of at least dihydroxy saturated alcohols, examples being ethylene glycol diacrylate, ethylene glycol dimethacrylate, 1,2-propanediol diacrylate, 1,2-propanediol dimethacrylate, 1,4-butanediol diacrylate, 1,4-butanediol dimethacrylate, hexanediol diacrylate, hexanediol dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, 3-methylpentyl glycol diacrylate, and 3-methylpentyl glycol dimethacrylate. Acrylates and methacrylates of alcohols having more than two OH groups can also be used as crosslinking agents, examples being trimethylolpropane triacrylate or trimethylolpropane trimethacrylate.
[0088] Preferably, the solid-based weight ratio of the olefinic unsaturated monomer M to the polymer A is preferably in the range of 4:1 to 1:4, particularly 3:1 to 1:3.
[0089] The adhesive system (B) according to the invention further comprises, by weight, 1% to 12% of at least one amine and / or amide having at least two hydroxyl groups based on the total weight of the olefinic unsaturated monomer M and polymer A.
[0090] Suitable amines having at least two hydroxyl groups are alkoxylated, preferably ethoxylated or propoxylated amines or alkylamines.
[0091] Suitable amines and / or amides having at least two hydroxyl groups are alkanolamines disclosed in DE 19729161, which are incorporated herein by reference as part of the disclosure of this invention.
[0092] The preferred amine is a β-hydroxyalkylamine of formula (I).
[0093] R 1 - N(R 2 ) - R 3 (I)
[0094] Where R 1 Hydrogen atoms, C1 to C 10 alkyl groups, C1 to C 10 β-hydroxyalkyl group or free radical of formula (II)
[0095] -(CH2CH2O) x (CH2CH(CH3)O) y -H(II)
[0096] in
[0097] In Equation II, the order of the alkoxide units is arbitrary, and x and y are independent integers from 0 to 100, the sum of x and y is greater than 1, and
[0098] R 2 and R 3 Independently, they are C1 to C 10 β-hydroxyalkyl group.
[0099] R is particularly preferred. 2 and R 3 Each is independently a C2 to C5 β-hydroxyalkyl group, and R 1 It can be a hydrogen atom, a C1 to C5 alkyl group, or a C2 to C5 β-hydroxyalkyl group.
[0100] Particularly preferred are diethanolamine, triethanolamine, diisopropanolamine, triisopropanolamine, methyldiethanolamine, butyldiethanolamine and methyldiisopropanolamine, especially triethanolamine.
[0101] Preferred β-hydroxyalkylamines with relatively high functionality, particularly at least diethoxylated amines having a molar amount of less than 1000 g / mol, such as diethanolamine, triethanolamine and ethoxylated diethylenetriamine, for example preferably stoichiometric ethoxylated diethylenetriamine, i.e., diethylenetriamine in which all NH hydrogen atoms are monoethoxylated on average.
[0102] Further preferred are amides having at least two hydroxyl groups. Suitable amides include β-hydroxyalkylamides, preferably β-hydroxyalkylamides of formula III as specified in U.S. Patent No. 5,143,582.
[0103]
[0104] The particularly preferred β-hydroxyalkylamides of the above formula are those of the following:
[0105] R 1 It is hydrogen, C1-C4-alkyl group or HO(R) 3 )2C(R 2 )2C-,
[0106] n and n' are both 1.
[0107] -A- is C2-C 10 -alkylene, branched C2-C 10 -alkylene, C5-C 14 - Cycloalkylene, arylene or alkylarylene
[0108] R 2 It is hydrogen.
[0109] Group R 3 One of them is hydrogen and the other is either hydrogen or a C1-C5 alkyl group.
[0110] Bis[N,N-di(2-hydroxyethyl)]hexamethylenediamide is particularly preferred.
[0111] The addition of an amine having at least two hydroxyl groups generally results in better curing of the compositions of the present invention at a given curing temperature, or, respectively, at a lower temperature for a given curing time. The amine and / or amide constitute 1% to 12% by weight, preferably 3% to 10% by weight, relative to the total weight of the olefinically unsaturated monomer M and the polymer A.
[0112] Additionally, reaction promoters can be added to the polymer dispersions of the present invention. Preferred such promoters are phosphorus compounds, particularly hypophosphite and its alkali metal and alkaline earth metal salts, or alkali metal tetrafluoroborates. Other reaction promoters that can be added include salts of Mn(II), Ca(II), Zn(II), Al(III), Sb(III), or Ti(IV), or strong acids such as p-toluenesulfonic acid, trichloroacetic acid, and chlorosulfonic acid. The reaction promoter is present in a weight fraction of 0.1% to 5% (preferably 0.1% to 2%) relative to the total weight of the olefinically unsaturated monomer M and polymer A.
[0113] The aqueous adhesive system (B) of the present invention is particularly preferred:
[0114] 90% to 99% by weight of the aqueous polymer dispersion (P) of the polymer
[0115] 0% to 2% emulsifier by weight,
[0116] 1% to 10% by weight of amines and / or amides having at least two hydroxyl groups.
[0117] 0% to 5% by weight of reaction accelerator
[0118] These quantities are based on the adhesive system (a) (solid).
[0119] When the above-mentioned adhesive system (B) is used to produce an aqueous glass coating composition, the aqueous glass coating composition may additionally include dyes, pigments, fillers, dispersants, thickeners, preservatives, film-forming aids, flow control and wetting aids, solvents, neutralizers, defoamers and light stabilizers.
[0120] The present invention also provides an aqueous container glass coating composition comprising...
[0121] (a) The adhesive system according to the invention (B)
[0122] (b) One or more defoamers
[0123] (c) Optionally one or more agglomerating agents
[0124] (d) Optionally one or more dyes, pigments and / or fillers, preferably one or more dyes and / or pigments and optional fillers.
[0125] (e) Optionally one or more other additives.
[0126] Preferably, any pigments and fillers present in the container glass coating composition have a particle size of not more than 50 µm according to DIN EN ISO 1524.
[0127] Defoamers are low surface tension liquids that exhibit controlled insolubility or incompatibility in the system to be defoamed, as well as positive penetration and positive spreading coefficients (Mannari, Patel, Understanding Coatings Raw Materials, Vincentz Verlag 2015, p. 254). The effectiveness of such liquid defoamers can be enhanced by adding finely dispersed hydrophobic particles, which contribute to destabilization by reducing cohesion. The main categories of defoamers used for water-based coatings are: inorganic oil-based defoamers, silicone defoamers, and fluorinated defoamers.
[0128] Coalescing agents will be apparent to those skilled in the art. Non-exclusive examples of coalescing agents include monoethers and monoesters of glycols, preferably glycols having at least one terminal hydroxyl group. Monoethers of ethylene glycol are readily available. Monoethers of propylene glycol are preferred in this category, particularly methyl, tert-butyl, n-butyl, and phenol monoethers of propylene glycol, dipropylene glycol, and tripropylene glycol.
[0129] In this context, pigments that may be used include, in principle, all organic and / or inorganic white and / or colored pigments familiar to those skilled in the art and with a particle size ≤10000 nm (Brock, Groteklaes, Mischke, Lehrbuch der Lacktechnologie 2nd ed., edited by U. Zorll, Vincentz Verlag 1998, p. 113).
[0130] In addition to inorganic pigments, the dispersion paint according to the present invention may also contain organic pigments or dyes, such as sepia, gamboge, Kassel brown, toluidine red, p-red, Hansa yellow, indigo, azo dyes, anthraquinones and indigo dyes, as well as dioxazine, quinacridone, phthalocyanine, isoindolinone and metal complex pigments. Synthetic white pigments with air inclusions to increase light scattering, such as Rhopaque, are also included. ® Dispersions are also suitable.
[0131] According to a preferred embodiment, the aqueous container glass coating composition comprises the following:
[0132] (a) The adhesive system according to the invention (B)
[0133] (b) One or more defoamers
[0134] (c) Optionally one or more agglomerating agents
[0135] (d) One or more dyes, pigments and / or fillers, preferably one or more dyes and / or pigments and optional fillers.
[0136] (e) Optionally one or more other additives.
[0137] Since one object of the present invention is to provide a formaldehyde-free adhesive system, it is preferred that the container glass coating composition is substantially free of resins containing N-hydroxymethyl groups.
[0138] Typically, any pigments and fillers present in waterborne container glass coating compositions have a particle size of not more than 50 µm, preferably ≤30 µm, and especially ≤20 µm, according to DIN EN ISO 1524.
[0139] The proportions of pigments and fillers in a container glass coating composition can be described in a well-known manner using pigment volume concentration (PVC). PVC describes the volume (V) of the pigment. P ) and the volume of the packing (V) F The ratio of the volume of the coating film to the total volume, which is determined by the volume of the adhesive system of the dried coating film (V). B The volume composition of pigments and fillers, expressed as a percentage:
[0140] PVC=(V P +V F )x 100 / (V P +V F +V B ).
[0141] The effect of the adhesive system according to the invention is particularly relevant in the case of pigmented container glass coating compositions having a PVC content of at least 5, especially at least 10. Preferably, the PVC content is no more than 50, especially 40, and particularly in the range of 5 to 40.
[0142] The water-based container glass coating composition is prepared by combining the components of the composition and forming a homogeneous mixture. In the presence of pigments and / or fillers, the high particle size present in the water-based paint is adjusted to a diameter of ≤50µm, preferably ≤30µm, and especially ≤10µm, according to DIN EN ISO 1524 (Paints, varnishes and printing inks - Determination of fineness of grind). Particle size adjustment is carried out, for example, by grinding as described in Paint and Surface Coatings, Theory and Practice, 2nd edition, edited by R. Lambourne and T.A. Strevens, Woodhead Publishing Limited, Cambridge England, 1999; page 117 and thereafter.
[0143] The compositions of the present invention do not release formaldehyde during the crosslinking process. Formaldehyde-free means that the compositions of the present invention do not contain a significant amount of formaldehyde and do not release a significant amount of formaldehyde during drying and / or curing. Typically, the compositions contain <100 ppm, preferably <10 ppm, of formaldehyde.
[0144] The viscosity of the adhesive system (based on a solids content of 40% by weight) is typically in the range of approximately 10 mPas to 4000 mPas, measured using a rotational viscometer at 23°C and 250 s according to DIN 53019. -1 Measured at the shear rate.
[0145] Using the coating composition according to the invention, a coating can be formed on the glass surface of a container glass article. The invention also relates to coating container glass articles that can be obtained by the method according to the invention.
[0146] Those skilled in the art will use the term "container glass" to refer to a type of glass used in the production of glass containers, such as bottles, jars, drinking vessels, and bowls. Container glass contrasts with flat glass (e.g., used for windows, glass doors, transparent walls, windshields) and fiberglass. Preferably, it is glass composed of 70% to 80% SiO2 (silicon dioxide) by weight.
[0147] Silicate glasses, such as soda-lime glass and borosilicate glass, are preferred container glasses. Soda-lime glass is particularly preferred.
[0148] Sodium-calcium glass (also known as "sodium-calcium silicate glass", "sodium-calcium glass" or "ordinary glass") belongs to the group of alkaline earth metal silicate glasses. Typical sodium-calcium glass consists of 71% to 75% sand (SiO2), 12% to 16% sodium oxide (Na2O), and 10% to 15% lime (CaO), based on total weight in each case.
[0149] Borosilicate glass consists of 70% to 80% by weight sand, 7% to 13% by weight boron trioxide, 4% to 8% by weight sodium oxide and / or potassium oxide, 2% to 7% by weight aluminum oxide, and 0% to 5% by weight of alkali metal oxides in each case, based on total weight. Therefore, these glasses are used in heat-resistant cookware, in lampshades, lamps, and light bulbs in the lighting industry, and in household items such as drinking glasses, coffee pots, storage containers, and baby bottles.
[0150] Glassware containers are containers made of glass that are typically used for storing and transporting food or liquids. Glassware containers come in a variety of shapes and sizes, including bottles and jars with screw-on or snap-on lids, corks, or metal caps, or drinking glasses. These glassware containers are commonly used for storing and preserving jams, jellies, sauces, oils, vinegars, beverages, and other foods. Preferred products are packaging containers made of glass.
[0151] Typically, glass containers are produced either by pressed glass (so-called pressed glass) or by blown glass. Pressed glass (also known as molded glass) is a type of glassware produced by pressing molten glass into a mold to create a specific shape or pattern. This differs from blown glass, which is formed by blowing air into molten glass to create a hollow shape.
[0152] Borosilicate glass containers are preferred for use in the pharmaceutical industry as ampoules and vials for packaging injectables, or as heavy-duty lampshades. These glass containers are also used as baking and casserole dishes, as well as other "fire-resistant" tableware.
[0153] Application can be done using methods commonly used in coating technology, such as roller coating, spraying, brushing, marble-look coating, or dip coating.
[0154] Spray coating involves introducing a coating composition onto a surface, such as the interior or exterior of a preformed article (especially a packaging container). Spraying preferably utilizes a nozzle capable of uniformly coating the interior or exterior of the preformed container. The sprayed preformed container is then heated to remove residual solvents and to harden the coating.
[0155] The thickness of the layer to be cured can be from 0.1µm to 2000µm, preferably from 1µm to 500µm, particularly preferably from 5µm to 200µm, and very particularly preferably from 5µm to 60µm (based on the material coating composition in a state where the solvent has been removed from the material coating composition).
[0156] Drying is familiar to those skilled in the art and is accomplished, for example, in a tunnel oven or by flash drying. Drying can also be carried out using NIR radiation, which refers herein to electromagnetic radiation with wavelengths ranging from 760 nm to 2.5 μm, preferably from 900 nm to 1500 nm. Drying can be carried out at temperatures from ambient to 100°C for periods ranging from several minutes to several days.
[0157] After drying, they can be cured in a conventional manner, preferably at a temperature in the range of 130°C to 180°C, more preferably 150°C to 180°C, and more preferably 140°C to 160°C. This curing typically takes 10 to 25 minutes.
[0158] Alternatively, if a shorter curing time is desired, such as from a few seconds to a few minutes, typically from 10 seconds to 5 minutes, then a higher temperature should be selected, i.e., between 200°C and 350°C (target temperature).
[0159] Upon heating, the water in the composition evaporates, and the composition solidifies (hardens). These processes can occur simultaneously or sequentially. In this context, solidification refers to a chemical change in the composition, such as crosslinking through the formation of covalent bonds, ionic interactions and clusters, and hydrogen bonds between different components of the composition. Solidification can also be accompanied by physical changes within the adhesive, such as, for example, phase rearrangement or phase inversion. An advantage of the compositions of the present invention is that they can be solidified at relatively low temperatures. The duration and temperature of heating affect the degree of solidification.
[0160] The cured coating according to the present invention has good elasticity, good adhesion of the resulting coating, high gloss, excellent surface hardness and good water resistance, and all its components are compatible.
[0161] The container glass articles coated according to the present invention can be easily cleaned during the recycling process. The coating film can be easily removed by an alkaline cleaning process, and the resulting transparent glass can then be recycled.
[0162] The following non-limiting embodiments are used to illustrate the present invention. Example
[0163] Unless the context otherwise requires, percentages are always expressed as weight percentages. The reported content refers to the content in aqueous solutions or dispersions. The expression "pphm (parts per hundred parts monomer)" indicates the weight percentage based on 100 parts by weight of monomer.
[0164] In the context of using water in this embodiment, demineralized water is used.
[0165] Measurement methods
[0166] Solids content is typically determined by drying a defined amount of the polymer aqueous dispersion (approximately 0.8 g) to constant weight at 130°C using a Mettler Toledo HR73 moisture analyzer. Two measurements are performed in each case, and the average of the two measurements is reported.
[0167] Weight-average particle size (Dw) was determined according to ISO 13321 using a high-performance particle size analyzer from Malvern at 22°C and a wavelength of 633 nm.
[0168] Viscosity :
[0169] The viscosity of the composition is up to 250 sec according to DIN 53019 in Anton Paar DSR 301. -1 The shear rate was determined at 23°C.
[0170] Example 1
[0171] 1a) Preparation of polymer A
[0172] 350 g of deionized water was added to a pressure reactor equipped with an anchor stirrer, and the mixture was heated to 100 °C under a nitrogen atmosphere. Upon reaching 100 °C, feed stream 1 was metered in over a 4-hour timeframe, and feed stream 2 was metered in over a 5-hour timeframe, both feeds introduced at a uniform rate while maintaining the temperature at 100 °C. After feed stream 1 was completed, the feed tank was rinsed with 25 g of deionized water and fed downwards into the reactor. After feed stream 2 was completed, the feed tank was rinsed with 25 g of deionized water and fed downwards into the reactor, and the contents were further post-polymerized at 100 °C for 2 hours. After the reaction was complete, the mixture was cooled to room temperature. During cooling, 332 g of deionized water was added. The resulting aqueous polymer solution had a solids content of 25% by weight, a pH of 2, and a 100s... -1 Viscosity at 306 mPas.
[0173] Feed flow 1:
[0174] 234.5g of methacrylic acid
[0175] 115.5g of acrylic acid
[0176] 227.5g of deionized water
[0177] Feed flow 2:
[0178] 135.0g of deionized water
[0179] 15.0g of sodium persulfate
[0180] 1b) Preparation of polymer dispersion (P)
[0181] 62 g of water and 468.2 g of the polymer A solution obtained in Example 1a) were added to a 2 L glass vessel equipped with an anchor stirrer (150 rpm), and the initial addition was heated to 90 °C. At 90 °C, 3 g of feed stream 2 was added. After waiting 5 minutes, at this temperature, feed stream 1 was metered in over a 3-hour time period at a constant rate, while the remainder of feed stream 2 was metered in over a 3.5-hour time period. Subsequently, after polymerization at this temperature for 15 minutes, 6 g of a 10 wt% aqueous solution of tert-butyl hydroperoxide and 7 g of a 13 wt% aqueous solution of acetone and sodium bisulfite were metered in over a 60-minute time period at a constant rate. The reactants were then cooled to room temperature. The solids content was 46.7% by weight.
[0182] Feed flow 1:
[0183] 130g of styrene
[0184] 75.4g of methyl methacrylate
[0185] 26g of n-butyl acrylate
[0186] 26g of 2-hydroxyethyl acrylate
[0187] 2.6g glycidyl methacrylate
[0188] Feed flow 2:
[0189] 20.7g of deionized water
[0190] 2.3g of sodium persulfate
[0191] 1c) Preparation of adhesive system B1
[0192] 28.3 g of an aqueous solution of 2,2',2''-triethanolamine (=triethanolamine) (82.2% by weight) was added to 800 g of the aqueous dispersion of Example 1b) under mechanical stirring for 5 min, and then further mixed for at least 20 min. The resulting binder system B1 has 48% non-volatile matter by weight, a pH of 3.8, and a viscosity of 100 s. -1 The value is 1050 mPas.
[0193] Solid adhesive system (B1) includes
[0194] Polymer P (total of monomers M) accounts for 64.9% by weight.
[0195] Polymer A, by weight, comprises 29.2% and
[0196] 5.9% amine by weight.
[0197] Example 2
[0198] 2b) Preparation of polymer dispersion P
[0199] 8 g of water and 668.9 g of the polymer A solution obtained in Example 1a) were added to a 2 L glass vessel equipped with an anchor stirrer (150 rpm), and the initial addition was heated to 90 °C. 3 g of feed stream 2 was added at 90 °C. After waiting 5 minutes, feed stream 1 was metered at this temperature over a 2 h 20 min time period, and the remainder of feed stream 2 was metered at the same time over a 2 h 50 min time period. Subsequently, after polymerization at this temperature for 15 min, 6 g of a 10 wt% aqueous solution of tert-butyl hydroperoxide and 7 g of a 13 wt% aqueous solution of acetone and sodium bisulfite were metered at the same time over a 60 min time period. The reactants were then cooled to room temperature. The solids content was 40.9% by weight.
[0200] Feed flow 1:
[0201] 100g of styrene
[0202] 56g of methyl methacrylate
[0203] 20g of n-butyl acrylate
[0204] 20g of 2-hydroxyethyl acrylate
[0205] 2g of glycidyl methacrylate
[0206] Feed flow 2:
[0207] 16.4g of deionized water
[0208] 1.8g of sodium persulfate
[0209] 2c) Preparation of adhesive system B2
[0210] 30.0 g of 2,2',2''-triethanolamine (=triethanolamine) was added to 800 g of the aqueous dispersion of Example 2b) under mechanical stirring for 5 min, and then further mixed for at least 20 min. The resulting binder system B2 has 43% nonvolatile matter by weight, a pH of 3.9, and a viscosity of 100 s. -1 The value is 1050 mPas.
[0211] Solid adhesive system (B2) includes
[0212] The polymer P (total of monomers M) accounts for 49.6% by weight.
[0213] Polymer A, by weight, comprises 42% polymer A, and
[0214] 8.4% amine by weight
[0215] Example 3
[0216] 3b) Preparation of polymer dispersion P
[0217] 151.7 g of water and 518.0 g of the polymer A solution obtained in Example 1a) were added to a 2 L glass vessel equipped with an anchor stirrer (150 rpm), and the initial addition was heated to 90 °C. Feed stream 1 was added at 90 °C. After waiting for 5 minutes, 3.7 g of feed stream 3 was added in one go, and then the remainder of feed stream 3 was metered in at a constant rate over a 3 h 25 min time period at 90 °C. Feed stream 2 was metered in at a constant rate over a 2 h 45 min time period 10 min after the start of feed stream 3. After feed stream 3 was completed, further polymerization was carried out at this temperature for 15 min; then, 5.6 g of a 10 wt% aqueous solution of tert-butyl hydroperoxide and 6.5 g of a 13 wt% aqueous solution of acetone and sodium bisulfite were metered in simultaneously over a 60 min time period at a constant rate. The reactants were then cooled to room temperature. The solids content was 40.2% by weight.
[0218] Feed flow 1:
[0219] 11.1g of styrene
[0220] 5.55g of n-butyl acrylate
[0221] 1.85g of 2-hydroxyethyl acrylate
[0222] Feed flow 2:
[0223] 111g of styrene
[0224] 64.4g of methyl methacrylate
[0225] 22.2g of n-butyl acrylate
[0226] 22.2g of 2-hydroxyethyl acrylate
[0227] 2.2g of glycidyl methacrylate
[0228] Feed flow 3:
[0229] 20g of deionized water
[0230] 2.2g of sodium persulfate
[0231] 3c) Preparation of adhesive system B3
[0232] 37.6 g of an aqueous solution of 2,2',2''-triethanolamine (=triethanolamine) (50% by weight) was added to 800 g of the aqueous dispersion of Example 3b) under mechanical stirring for 5 min, and then mixed further for at least 20 min. The resulting binder system B3 has 41% nonvolatile matter by weight, a pH of 3.8, and a viscosity of 100 s. -1 The value is 180 mPas.
[0233] Solid adhesive system (B3) includes
[0234] Polymer P (total of monomers M) accounts for 61.4% by weight.
[0235] Polymer A, by weight, comprises 33.1% and
[0236] 5.5% amine by weight
[0237] Example 4
[0238] 4b) Preparation of polymer dispersion P
[0239] Add 77.9g of water and 9.5g of Disponil to a 2L glass container equipped with an anchor stirrer (150rpm). ® The polymer A solution obtained from FES 77 (from BASF, an alkyl ether sulfate surfactant) and 532 g of Example 1a) was heated to 93°C. At 93°C, 10.6 g of feed stream 2 was added. After waiting 2 minutes, at this temperature, feed stream 1 was metered in over a 3 h 20 min time period at a constant rate, while the remainder of feed stream 2 was metered in over a 3 h 50 min time period. Subsequently, after polymerization at this temperature for 15 minutes, 5.7 g of a 10 wt% aqueous solution of tert-butyl hydroperoxide and 6.7 g of a 13 wt% aqueous solution of acetone and sodium bisulfite were metered in over a 45 min time period at a constant rate. The reactants were then cooled to room temperature. The solids content was 39.8% by weight.
[0240] Feed flow 1:
[0241] 123.5g of styrene
[0242] 69.5g of methyl methacrylate
[0243] 24.7g of n-butyl acrylate
[0244] 26.6g of 2-hydroxyethyl acrylate
[0245] 2.7g glycidyl methacrylate
[0246] Feed flow 2:
[0247] 84.5g of deionized water
[0248] 2.2g of sodium persulfate
[0249] 4c) Preparation of adhesive system B4
[0250] 37 g of an aqueous solution of 2,2',2''-triethanolamine (=triethanolamine) (50% by weight) was added to 800 g of the aqueous dispersion of Example 4b) under mechanical stirring for 5 min, and then further mixed for at least 20 min. The resulting binder system B4 has 39% non-volatile matter by weight, a pH of 3.9, and a viscosity of 100 s. -1 The value below is 200 mPas.
[0251] Solid adhesive system (B4) contains
[0252] Polymer P (total of monomers M) by weight is 61.5%.
[0253] Polymer A, by weight, comprises 33.0% and
[0254] 5.5% amine by weight
[0255] Example 5
[0256] 5b) Preparation of polymer dispersion P
[0257] 135.0 g of water, 4.5 g of dodecylbenzenesulfonic acid, and 840 g of polymer A (25% concentration by weight) were added to a 2 L glass vessel equipped with an anchor stirrer (150 rpm), and the initial addition was heated to 93 °C. At 93 °C, 24.0 g of feed stream 2 was added. After waiting 2 minutes, at this temperature, feed stream 1 was metered in at a constant rate over a 3 h time period, while the remainder of feed stream 2 was metered in simultaneously over a 3 h 30 min time period. Polymerization was then carried out at this temperature for 75 minutes, after which the reactants were cooled to room temperature. The solids content was 40.4%.
[0258] Feed flow 1:
[0259] 132.0g of n-butyl methacrylate
[0260] 132.0g of methyl methacrylate
[0261] 58.2g of n-butyl acrylate
[0262] 69.2g of 2-hydroxyethyl methacrylate
[0263] Feed flow 2:
[0264] 117.0g of deionized water
[0265] 3.0g sodium persulfate
[0266] 5c) Preparation of adhesive system B5
[0267] 19.4 g of an aqueous solution (50% by weight) of N,N,N',N'-tetratetra(2-hydroxyethyl)hexamethylenediamine (Primid XL-552 from EMS Chemie) was added to 400 g of the aqueous dispersion of Example 5b) under mechanical stirring for 5 min and then mixed further for at least 30 min. The resulting binder system B5 has 40.8% non-volatile matter by weight.
[0268] Application testing :
[0269] Pendulum hardness
[0270] The hardness of the coating was determined using a König type pendulum hardness tester according to DIN EN ISO 1522. Results were recorded in terms of the number of oscillations. For this type of coating, a hardness above 135 oscillations was considered good, and a hardness above 150 oscillations was considered very good.
[0271] Adhesion
[0272] The adhesion of the coating to glass was tested using a cross-cut test according to DIN EN ISO 2409:2013-06. Result 0 is the best, and result 5 is the worst.
[0273] Water resistance (24h / RT) :
[0274] The coated glass plate was placed in a demineralized water bath at ambient temperature, with approximately 50% to 65% of the coated portion immersed in water. After 24 hours, the glass plate was removed and dried with paper towels. After a 2-minute regeneration time, the cross-cut adhesion of the immersed area (test area) was checked according to DIN EN ISO 2409:2013-06; and the mechanical integrity of the membrane was assessed by scratching with a fingernail. The degree of bubbling was assessed according to DIN EN ISO 4628-2:2004-01. After regeneration at RT for 1 hour, the test area was checked again. In addition, any turbidity, discoloration, haze, or other defects in the dried test area were visually evaluated.
[0275] Water resistance (30 min / 70℃) :
[0276] The coated glass plate is placed in a demineralized water bath preheated to 70°C, with approximately 50% to 65% of the coating submerged in water. The glass plate is then kept submerged for 30 minutes while maintaining the water temperature at 70°C. The glass plate is then removed and dried with a paper towel. After a 2-minute regeneration time, the cross-cut adhesion of the submerged area (test area) is checked according to DIN EN ISO 2409:2013-06; and the mechanical integrity of the membrane is assessed by scratching with a fingernail. The degree of bubbling is assessed according to DIN EN ISO 4628-2:2004-01. The test area is re-checked after 20 minutes of regeneration at RT. Furthermore, any turbidity, discoloration, haze, or other defects in the dried test area are visually evaluated.
[0277] Tolerance to mixtures of solvents and plasticizers (24h / RT)
[0278] The test solution used for this test is a mixture of solvent and plasticizer as shown below.
[0279] 70 parts by weight of ethanol (99%)
[0280] 20 parts by weight of turpentine
[0281] 10 parts by weight of dibutyl phthalate
[0282] The coated glass plate is placed in a vessel containing the test solution, maintained at 55°C, with approximately 50% to 60% immersion in the solution. During the test, the vessel is covered to prevent evaporation of the test solution. After 24 hours at 55°C, the glass plate is removed and dried with disposable paper towels. After a 2-minute regeneration time, the cross-cut adhesion of the test area is checked according to DIN EN ISO 2409; and the mechanical integrity of the film is assessed by scratching with a fingernail. The degree of bubbling is evaluated according to DIN ENIOS 4628-2:2004-01. After 1 hour of regeneration at RT, the check is repeated on the test area. Furthermore, any turbidity, discoloration, haze, or other defects in the dried test area are visually evaluated.
[0283] Preparation and application of water-based glass coating compositions :
[0284] Preparation of test substrate (glass plate)
[0285] The coating was tested using a flat glass plate (200mm × 80mm × 3mm). The glass plate was cleaned with Spülfix BASF (Deutsche Hahnerol GmbH, 30453 Hannover, Germany), then thoroughly rinsed with deionized water, and then dried before coating.
[0286] Coating Example 1: Composition of the coating using adhesive system B1
[0287] Two components of the coating were tested using adhesive system B1 as shown in Table 1. A mixture of slowly added solvent and water (serial numbers 2, 3, and 4) was added to adhesive system B1 (serial number 1) over 2 to 3 minutes with mechanical stirring, and the mixture was homogenized for 10 minutes. The mixture was then allowed to stand under ambient conditions for at least one day. The additive in serial number 5 was slowly added to the mixture with stirring and mixed for 1 to 2 minutes; the paint was then filtered through a 15-micron sieve and applied to a glass plate (flat glass) with a wet film thickness of 50 microns using a doctor blade applicator. After flash evaporation at room temperature for 10 minutes, it was cured at 180°C for 15 minutes (object temperature).
[0288] Table 1: Composition of coatings using adhesive system B1
[0289]
[0290] 1) Solvennon DPnB: Di(propylene glycol) butyl ether
[0291] 2) Silquest A-187: (3-glycidoxypropyl)trimethoxysilane
[0292] 3) Dynasylan AMEO: (3-aminopropyl)triethoxysilane
[0293] The test results of the coating prepared in Coating Example 1 are shown in Table 2.
[0294] Table 2: Test results of coatings using adhesive system B1
[0295]
[0296] Coating Example 2: Composition of the coating using adhesive system B2
[0297] The composition of the coating using adhesive system B2 is shown in Table 3. This coating was prepared and applied in the same manner as in Coating Example 1, but with adhesive system B2 used instead of B1.
[0298] Table 3: Composition of coatings using adhesive system B2
[0299]
[0300] The test results of the coating prepared in Coating Example 2 are shown in Table 4.
[0301] Table 4: Test results of coatings using adhesive system B2
[0302]
[0303] Coating Example 3: Composition of the coating using adhesive system B3
[0304] The composition of the coating using adhesive system B3 is shown in Table 5. The solvent mixture (serial numbers 2 and 3) was slowly added to adhesive system B3 (serial number 1) over 2 to 3 minutes with mechanical stirring, and homogenized for 10 minutes. The mixture was then allowed to stand under ambient conditions for at least one day. The additive from serial number 4 was slowly added to the mixture with stirring and mixed for 1 to 2 minutes; the paint was then filtered through a 15-micron sieve and applied to a glass plate (flat glass, air side) with a wet film thickness of 50 microns using a doctor blade applicator. After flash evaporation at room temperature for 10 minutes, it was cured at 180°C for 15 minutes (object temperature).
[0305] Table 5: Compositions for coatings using adhesive system B3
[0306]
[0307] The test results of the coating prepared in Coating Example 3 are shown in Table 6.
[0308] Table 6: Test results of coatings using adhesive system B3
[0309]
[0310] Coating Example 4: Composition of the coating using adhesive system B4
[0311] The composition of the coating using adhesive system B4 is shown in Table 7. The solvent mixture (serial numbers 2 and 3) was slowly added to adhesive system B4 (serial number 1) over 2 to 3 minutes with mechanical stirring, and the mixture was homogenized for 10 minutes. The mixture was then allowed to stand under ambient conditions for at least one day. Silquest A-187 was then slowly added to the mixture with stirring. ™ (As a 1:1 mixture with butyl diethylene glycol) (Serial No. 4), and mix for 1 to 2 minutes; then filter the paint through a 15-micron sieve and apply it to a glass plate (flat glass, air side) with a wet film thickness of 50 microns using a doctor blade applicator. After flash evaporation at room temperature for 10 minutes, cure it at 180°C for 15 minutes (object temperature).
[0312] Table 7: Combinations of coatings using adhesive system B4
[0313]
[0314] The test results of the coating prepared in Coating Example 4 are shown in Table 8.
[0315] Table 8: Test results of coatings using adhesive system B4
[0316]
[0317] Coating Example 5: Preparation and application of a coating using adhesive system B5
[0318] The composition of the coating using adhesive system B5 is shown in Table 9. The solvent mixture (serial numbers 2 and 3) was slowly added to adhesive system B5 (serial number 1) over 2 to 3 minutes with mechanical stirring, and the mixture was homogenized for 10 minutes. The mixture was then allowed to stand under ambient conditions for at least one day. Silquest A-187 was then slowly added to the mixture with stirring. ™ (As a 1:1 mixture with butyl diethylene glycol) (Serial No. 4), and mix for 1 to 2 minutes; then filter the paint through a 15-micron sieve and apply it to a glass plate (flat glass, air side) with a wet film thickness of 50 microns using a doctor blade applicator. After flash evaporation at room temperature for 10 minutes, cure it at 180°C for 15 minutes (object temperature).
[0319] Table 9: Compositions for coatings using adhesive system B5
[0320]
[0321] The test results of the coating prepared in Coating Example 5 are shown in Table 10.
[0322] Table 10: Test results of coatings using adhesive system B5
[0323]
[0324] Comparative Examples: Preparation and Application of Comparative Coating Systems Using Melamine Crosslinking Agent (C)
[0325] A comparative coating system (C) was prepared using an aqueous polymer dispersion of hydroxyl-functionalized styrene acrylate crosslinked with highly methanol-etherified melamine-formaldehyde resin (HMMF) (OH-Disp). OH-Disp had a solids content of 43.5% by weight, an acid value of 60 mg KOH / g based on the solids polymer, and a hydroxyl value of 42 mg KOH / g based on the solids. HMMF had a solids content of 96%. The composition is shown in Table 11. Defoamer (Serial No. 2), distilled water (Serial No. 3), and HMMF (Serial No. 4) were slowly added to OH-Disp (Serial No. 1) over 2 to 3 minutes with mechanical stirring, and the mixture was homogenized for 10 minutes. The mixture was then allowed to stand under ambient conditions for at least one day. Silquest A-187 was then slowly added to the mixture with stirring. ™ (Serial No. 5), and mix for 1 to 2 minutes; then filter the paint through a 15-micron sieve and apply it to a glass plate (flat glass, air side) with a wet film thickness of 50 microns using a doctor blade applicator. After flash evaporation at room temperature for 10 minutes, cure it at 180°C for 15 minutes (object temperature).
[0326] Table 11: Comparison of the composition of coating system C
[0327]
[0328] The test results of the coatings prepared in the comparative coating examples are shown in Table 12.
[0329] Table 12: Test results of the comparative coating systems
[0330]
Claims
1. A method, the method comprising: A coating composition comprising an aqueous adhesive system (B) is provided, wherein the adhesive system (B) comprises (a) Aqueous polymer dispersion (P), and (b) at least one amine and / or amide having at least two hydroxyl groups, based on 1% to 12% by weight of the total weight of the olefinically unsaturated monomer M and polymer A. The aqueous polymer dispersion (P) is prepared by free radical-initiated emulsion polymerization of the following olefinically unsaturated monomer M in an aqueous medium in the presence of polymer A: Styrene and (meth)acrylic acid C1-C by weight: 65% to 95% 10 -Alkyl esters and / or (meth)acrylic acid C5-C 10 -Cycloalkyl esters; One or more hydroxyl-functionalized (meth)acrylates, (meth)acrylates glycidyl esters and / or (meth)acrylamides, by weight, comprising 5% to 35% of the following: One or more mono-olefin unsaturated carboxylic acids and / or mono-olefin unsaturated sulfonic acids, by weight, from 0% to 5%. One or more diene-bonded unsaturated monomers, comprising 0% to 2% by weight, and The total amount of the monomer M is 100% by weight. The polymer A has the following monomeric structural units: At least one olefinic unsaturated monocarboxylic acid and / or dicarboxylic acid (monomer A1) in an amount of 80% to 100% by weight, and From 0% to 20% by weight of at least one other olefinic unsaturated monomer (monomer A2) different from said monomer A1. The amount is based on the total amount of all monomeric structural units in polymer A in each case. The coating composition is applied to the glass surface of a container glass article to form a coating, and the coating is cured by treating the coating at a temperature in the range of 130°C to 350°C.
2. The method according to claim 1, wherein the aqueous dispersion (P) is prepared by polymerization of the following monomer M: Styrene and (meth)acrylic acid C1-C by weight: 80% to 95% 10 -Alkyl esters and / or (meth)acrylic acid C5-C 10 -Cycloalkyl esters; 5% to 20% by weight of one or more (meth)acrylate hydroxy (C2-C4)-alkyl esters, (meth)acrylate glycidyl esters and / or (meth)acrylamide, One or more mono-olefin unsaturated carboxylic acids and / or mono-olefin unsaturated sulfonic acids, by weight, from 0% to 5%. One or more diene-bonded unsaturated monomers, comprising 0% to 2% by weight, and The total amount of the monomer M is 100% by weight.
3. The method according to claim 1 or 2, wherein the aqueous dispersion (P) is prepared by polymerization of the following monomer M: 80% to 95% by weight of one or more monomers M1, wherein said one or more monomers M1 are selected from the group consisting of styrene, C1-C8 alkyl esters of (meth)acrylate and cyclohexyl methacrylate. 5% to 20% by weight of one or more monomers M2, wherein the one or more monomers M2 are selected from the group consisting of hydroxy (C2-C4)-alkyl esters of (meth)acrylate, glycidyl esters of (meth)acrylate, and (meth)acrylamide. One or more monomers M3, comprising 0% to 5% by weight, wherein the one or more monomers M3 are selected from the group consisting of monoene-bonded unsaturated carboxylic acids and monoene-bonded unsaturated sulfonic acids. One or more diene-bonded unsaturated monomers M4, comprising 0% to 2% by weight, and The total amount of the monomer M is 100% by weight.
4. The method according to any one of claims 1 to 3, wherein the aqueous dispersion (P) is prepared by polymerization of the following monomer M: 80% to 95% by weight of one or more monomers M1, wherein the one or more monomers M1 are selected from the group consisting of styrene, methyl methacrylate, 2-octyl acrylate, 2-ethylhexyl acrylate and (meth)acrylate n-butyl acrylate; 5% to 20% by weight of one or more monomers M2, wherein the one or more monomers M2 are selected from the group consisting of hydroxyethyl (meth)acrylate and glycidyl (meth)acrylate. One or more monomers M3, comprising 0% to 5% by weight, wherein the one or more monomers M3 are selected from the group consisting of monoene-bonded unsaturated carboxylic acids and monoene-bonded unsaturated sulfonic acids. One or more diene-bonded unsaturated monomers M4, comprising 0% to 2% by weight, and The total amount of the monomer M is 100% by weight.
5. The method according to any one of claims 1 to 4, wherein polymer A has the following monomeric structural units: 80% to 100% by weight of acrylic acid, methacrylic acid and / or itaconic acid Maleic acid, 0% to 20% by weight 0% to 10% by weight of at least one other monomer different from said monomer A1; The amount is based on the total amount of all monomeric structural units in polymer A in each case.
6. The method according to any one of claims 1 to 5, wherein the solid-based weight ratio of the olefinic unsaturated monomer M to the polymer A is in the range of 4:1 to 1:
4.
7. The method according to any one of claims 1 to 6, wherein the amine having at least two hydroxyl groups is selected from the group consisting of diethanolamine, triethanolamine, diisopropanolamine, triisopropanolamine, methyldiethanolamine, butyldiethanolamine, and methyldiisopropanolamine.
8. The method according to any one of claims 1 to 7, wherein at least one of the amides having at least two hydroxyl groups is a β-hydroxyalkylamide.
9. The method according to any one of claims 1 to 8, wherein the container glass is soda-lime glass or borosilicate glass.
10. The method according to any one of claims 1 to 9, wherein the thickness of the cured coating is from 0.1 µm to 500 µm.
11. A coated container glass article, said coated container glass article being obtainable by the method according to any one of claims 1 to 10.
12. The coated container glass article according to claim 11, wherein the article is a packaging container.
13. A water-based container glass coating composition, said water-based container glass coating composition comprising (a) The adhesive system according to any one of claims 1 to 9 (B) (b) One or more defoamers (c) Optionally one or more agglomerating agents (d) Optionally one or more dyes, pigments and / or fillers, preferably one or more dyes and / or pigments and optional fillers. (e) Optionally one or more other additives.
14. Use of the coating composition according to claim 14 for coating the glass surface of a container glass article.
Citation Information
Patent Citations
thermally curable, aqueous compositions
DE19729161A1
Method for applying a primer coating to glass containers
US20230101908A1
Heat-resistant nonwoven fabrics
US5143582A
Thermohardening polymer dispersion
US6841608B1